2018
DOI: 10.28991/cej-03091158
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Green Roofs and Green Walls on Energy Consumption and Indoor Comfort in Arid Climates

Abstract: Increased urbanization have many negative effects on human well-being, city infrastructure, electricity usage and the increase of indoor temperatures. A solution may be to retrofit existing buildings, with implementing a vegetated layer to roofs and walls, this may enhance building performance, reduce consumption and improve indoor comfort. Cities with tall buildings may be more adequate to implement a green-wall as it have more area to make impact. This paper examines the energy reduction advantages of adding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 34 publications
0
8
0
2
Order By: Relevance
“…The measurements taken to reduce energy consumption in residential building should not affect thermal comfort conditions. Some authors have suggested and studied the effect of facade shading and green roofs in conserving thermal comfort with less consumed energy [14][15][16]. These different modeling techniques have different strengths, weaknesses, capabilities, and applicabilities.…”
Section: Overview Of Modeling Methodologiesmentioning
confidence: 99%
“…The measurements taken to reduce energy consumption in residential building should not affect thermal comfort conditions. Some authors have suggested and studied the effect of facade shading and green roofs in conserving thermal comfort with less consumed energy [14][15][16]. These different modeling techniques have different strengths, weaknesses, capabilities, and applicabilities.…”
Section: Overview Of Modeling Methodologiesmentioning
confidence: 99%
“…They also meet the needs of industry. Summer peaks in electricity consumption are mostly driven by temperature, as illustrated by the increasing sales of air conditioning and ventilation systems for several decades (Wahba et al, 2018). The use of air conditioning in cars, which requires an additional amount of fuel, could also contribute to the increase in NO x emissions in summer.…”
Section: Annual Cycle and Comparison To Inventoriesmentioning
confidence: 99%
“…Water 2022, 14, 2496 31 of 42 analysis [72]. EnergyPlus and DesignBuilder are more suitable for building and indoor scales [73][74][75]. As there are more small-scale UGI studies, the use of software for the building scales analysis is thus more common.…”
Section: Data Analysis Software and Modelsmentioning
confidence: 99%